The influence of different exercise intensities on kicking accuracy and velocity in soccer players - Ferraz, R.; van den Tillaar, R.; Marques, M. C. (Journal of Sport and Health Science, 2017)
Purpose: The aim of this study was to investigate the influence of different exercise intensities induced by a soccer specific protocol on kicking performance in soccer players. Methods: Twelve semi-professional male soccer players participated in this study and performed maximal instep kicks before and after the implementation of an exercise protocol to determine the influence of different intensities upon kicking ball velocity and the target-hitting accuracy. Results: Analysis of variance designs with repeated measures showed that maximal ball velocity was affected only after the most intense circuit (F(6, 66)=2.3; p=0.041; 2=0.18), while accuracy was not affected in the protocol (F(6, 66)=0.19; p=0.98; 2=0.02). Low and moderate intensities did not affect accuracy or kicking ball velocity. Conclusion: These findings suggest that kicking ball velocity is influenced by high-exercise intensities. Low and moderate exercise intensities do not affect the performance of the kick, and intensity does not influence accuracy. Otherwise, it is possible that other mechanisms (not only physiological) may influence players during the exercise.